(3QSGdI JbdjO Scjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce HGdMb hTcQJ YHO g GdEeGe GdgGOi hdi GdNdb ef GdYHO GdebJfi HgGA GdOjf hdSGf GdeDefjf s
(3BNQgG (B:s
(3aYdjc MajX jSeY bhdc hjQGc aCMeO Gdehdi Ld PcQg Ydi LRjd ehGgHg Je GdJbdjO HMhd Gdehdi hbhJg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B46s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis